Super-rapid quantitation of the production of HIV-1 harboring a luminescent peptide tag - Ozono, Seiya; Zhang, Yanzhao; Tobiume, Minoru; Kishigami, Satoshi; Tokunaga, Kenzo (bioRxiv, 2020)
In virological studies using HIV-1 proviral clones, virus production is normally monitored by either an RT assay or a p24 antigen capture ELISA. However, these assays are costly and time-consuming for routine handling of a large number of HIV-1 samples. In addition, sample dilution is always required in ELISA to determine p24 protein levels because of the very narrow range of detectable concentrations in this assay. Here, we establish a novel HIV-1 production assay system to solve the aforementioned problems by using a recently developed small peptide tag called HiBiT. First, we constructed a novel full-length proviral HIV-1 DNA clone and a lentiviral packaging vector in which the HiBiT tag was added to the C terminus of the integrase. Tagging the integrase with the HiBiT sequence did not impede the production or infectivity of the resultant viruses. Electron microscopy revealed normal morphology of the virus particles. Most importantly, by comparing between ELISA and the HiBiT luciferase assay, we successfully obtained an excellent linear correlation between p24 concentrations and HiBiT-based luciferase activity. Overall, we conclude that HiBiT-tagged viruses can replace the parental HIV-1 and lentiviral vectors, which enables us to perform a super-rapid, inexpensive, convenient, simple, and highly accurate quantitative assay for HIV-1 production. Competing Interest Statement The authors have declared no competing interest.